Analysis of Effectiveness in Distance Learning in Tahfidz Lessons - Martin, Jayshree; Fang, Wang; Brunel, Benjamin (Yayasan Pendidikan Islam Daarut Thufulah, 2023)
For those who adhere firmly to Al Quran, Allah will reward them and their status will be increased by Allah SWT. This research aims to discuss the effectiveness of tahfidz learning over long distances at Musholla Nurul Huda, Indudur nagari, Subdistrict IX, Koto Sungai Lasi, Solok Regency. This research aims to find out whether tahfidz suadah lessons are effective or not. The method used by researchers in this research is a qualitative research method with a descriptive approach. With researchers using this qualitative method, researchers can obtain accurate data. The method of data collection that the researcher uses is observation, interviews, and documentation. For the basis of the data, the triangulation technique is used which is one of the approaches used to dig and perform qualitative data processing techniques. The tahfidz learning system at Musholla Nurul Huda has not been effective because there are obstacles that make distance learning not run optimally. The lack of facilities and infrastructure in distance learning which is not yet adequate, and the large amount of money spent to buy internet quota, and the network which is difficult to guess is sometimes high and then weak due to being in the countryside. So that the learning given by the teacher is not 100% smooth or effective.